Asbabun Nuzul in The Tafsir of Al-Munir Wahbah Azzuhaili - Widya Salsa, Dela; Misna, Eni; Putri, Nazua Amelia; Pulungan, M. Haris; Halomoan, Panda Jaya; Sipahutar, Yura Marizka; Damanik, Agusman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to explore the urgency and application of Asbabun Nuzul in Syekh Wahbah az-Zuhaili's Tafsir Al-Munir, one of the most influential commentaries on the Qur'an in the Islamic world. Asbabun Nuzul is a study of the historical background of the revelation of the verses of the Koran, which is an important key in understanding the meaning, context and legal objectives contained in these verses. This research focuses on analyzing the interpretive methods used by Sheikh Wahbah az-Zuhaili in integrating Asbabun Nuzul into his tafsir, as well as identifying the contribution of this approach in explaining the relevance of the verses of the Qur'an to modern situations. Through a descriptive-analytical approach, this research examines the brief biography of Sheikh Wahbah az-Zuhaili, his interpretation method, as well as examples of the application of Asbabun Nuzul to certain verses in Tafsir Al-Munir. The research results show that Asbabun Nuzul plays a strategic role in the interpretation of Al-Munir, not only in contextualizing the meaning of the verse but also in building a legal foundation that is in accordance with sharia principles. Apart from that, Sheikh Wahbah az-Zuhaili's interpretive method which is comprehensive, systematic and based on a contextual approach makes a significant contribution in enriching the treasures of Al-Qur'an exegesis studies. It is hoped that this research will provide new insight into the importance of understanding the historical context of Al-Qur'an verses in interpretation, as well as strengthening understanding of Al-Munir's interpretation as one of the main references in modern tafsir studies.